Vasovagal Oscillations and Vasovagal Responses Produced by the Vestibulo-Sympathetic Reflex in the Rat - Yakushin, Sergei B.; Martinelli, Giorgio; Raphan, Theodore; Xiang, Yongqing; Holstein, Gay R.; Cohen, Bernard (Frontiers in Neurology, 2014)
Sinusoidal galvanic vestibular stimulation (sGVS) induces oscillations in blood pressure (BP) and heart rate (HR) i.e., vasovagal oscillations, and decreases in BP and HR i.e., vasovagal responses, in isoflurane-anesthetized rats. We determined the characteristics of the vasovagal oscillations, assessed their role in the generation of vasovagal responses and determined whether they could be induced by monaural as well as by binaural sGVS and by oscillation in pitch. Wavelet analyses were used to determine the power distributions of the waveforms. Monaural and binaural sGVS and pitch generated vasovagal oscillations at the frequency and at twice the frequency of stimulation. Vasovagal oscillations and vasovagal responses were maximally induced at low stimulus frequencies (0.025-0.05 Hz). The oscillations were attenuated and the responses were rarely induced at higher stimulus frequencies. Vasovagal oscillations could occur without induction of vasovagal responses, but vasovagal responses were always associated with a vasovagal oscillation. We posit that the vasovagal oscillations originate in a low frequency band that, when appropriately activated by strong sympathetic stimulation, can generate vasovagal oscillations as a precursor for vasovagal responses and syncope. We further suggest that the activity responsible for the vasovagal oscillations arises in low frequency, otolith neurons with orientation vectors close to the vertical axis of the head. These neurons are likely to provide critical input to the Vestibulo-Sympathetic Reflex to increase BP and HR upon changes in head position relative to gravity, and to contribute to the production of vasovagal oscillations and vasovagal responses and syncope when the baroreflex is inactivated.